1999
DOI: 10.1159/000022097
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes of the Kidneys: Pharmacological Implications

Abstract: About 40% of the intoxications after drug administration occur in the elderly. A significant proportion of the disease states in elderly patients is related to adverse reactions to prescribed drugs. Declining renal function, a reduction in both renal blood flow and glomerular filtration rate, is a major contributor to drug toxicity in the elderly. Therefore, a review (based on newer papers from Medline) of age-dependent changes of the kidneys and their consequences for drug therapy in geriatric patients is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(112 citation statements)
references
References 56 publications
3
106
0
3
Order By: Relevance
“…Aging was reported to be associated with reductions in hepatic and renal function and alterations in plasma protein concentration. 25,26) However, age-related changes in the physiology of the liver and kidney would not affect aprepitant pharmacokinetics because patients enrolled in this study had normal hepatic and renal function regardless of their age. With respect to gender, our result supported that of the report of Nakade et al 10) which found that gender had no significant effect on aprepitant pharmacokinetics.…”
Section: Discussionmentioning
confidence: 97%
“…Aging was reported to be associated with reductions in hepatic and renal function and alterations in plasma protein concentration. 25,26) However, age-related changes in the physiology of the liver and kidney would not affect aprepitant pharmacokinetics because patients enrolled in this study had normal hepatic and renal function regardless of their age. With respect to gender, our result supported that of the report of Nakade et al 10) which found that gender had no significant effect on aprepitant pharmacokinetics.…”
Section: Discussionmentioning
confidence: 97%
“…Prevalence of declining renal function in aging is recognized as renal mass decreases by 20 to 25 % between the ages of 30 and 80 years (Beck 1998). Age-related accumulation of extracellular matrix, expansion of glomerular mesangium, and alteration of tubular epithelial transporters are also commonly reported (Muhlberg and Platt 1999). These factors contribute to an overall decline in glomerular filtration rate and impairment of tubular re-absorptive function that compromises the ability of kidneys to maintain proper extracellular fluid volume and composition.…”
Section: Discussionmentioning
confidence: 99%
“…In long-term care residents with GFR B/50 ml/min, 45% of the prescribed drugs with mainly renal elimination were dosed inappropriately relative to GFR (22). A GFR of B/40 ml/min predicted elevated plasma levels for several commonly used drugs (enalapril, cefotaxime, frusemide, spironolactone, hydrochlorothiazide) with a mean sensitivity of 90% and specificity of 83% (23). Among frequently prescribed antibiotics, a 34% dosing error rate relative to GFR has been reported (24).…”
Section: Discussionmentioning
confidence: 99%